The Preoperative Supplementation With Vitamin D Attenuated Pain Intensity and Reduced the Level of Pro-inflammatory Markers in Patients After Posterior Lumbar Interbody Fusion - Krasowska, Katarzyna; Skrobot, Wojciech; Liedtke, Ewelina; Sawicki, Piotr; Flis, Damian Jozef; Dzik, Katarzyna Patrycja; Libionka, Witold; Kloc, Wojciech; Kaczor, Jan Jacek (Frontiers in Pharmacology, 2019)
Abstract: The aim of this experimental study was to assess whether five weeks preoperative supplementation with vitamin D will affect the intensity of pain and level of inflammatory markers in patients undergoing posterior lumbar interbody fusion (PLIF) followed by rehabilitation. 42 patients were divided by double-blind randomization into two groups: supplemented (SUPL) vitamin D (3200 IU dose of vitamin D/day for 5 weeks) and placebo group (PL) treated with vegetable oil. The 10-week program of early rehabilitation (3 times a week) was initiated 4 weeks following PLIF. Measurements of serum 25(OH)D3 and CRP, IL-6, TNF-α, and IL-10 were performed. Pain intensity was measured using VAS. After supplementation with vitamin D serum concentration of 25(OH)D3 significantly increased in the SUPL group (*p<0.005) and was significantly higher as compared to the PL group (*p<0.001). Significant reduction in pain intensity was observed 4 weeks after surgery and after rehabilitation in both groups. In the SUPL group serum CRP and IL-6 concentration significantly decreased after rehabilitation compared with postsurgical level (ap<0.04). The level of TNF-α was significantly lower after rehabilitation only in the supplemented group (*p<0.02). There were no significant changes in IL-10 level in both groups during the study. Our data indicate that supplementation with vitamin D may reduce systemic inflammation and combined with surgery and early postsurgical rehabilitation may decrease the intensity of pain in LBP patients undergoing PLIF. Data indicate that LBP patients undergoing spine surgery should use vitamin D perioperatively as a supplement.